Yfiler® Plus amplification kit validation and calculation of forensic parameters for two Austrian populations. (March 2016) - Pickrahn, Ines; Müller, Eva; Zahrer, Waltraud; Dunkelmann, Bettina; Cemper-Kiesslich, Jan; Kreindl, Gabriele; Neuhuber, Franz
Highlights: A validation of the AmpFISTR ® Yfiler ® Plus kit was carried out. Results/performance were compared with Yfiler ® data. The Yfiler ® Plus kit appeared to be unimpaired by typical inhibitors. Y-STR profiles of 425 unrelated males from two Austrian populations are shown. Forensic parameters were calculated and compared for four Y-STR marker sets. The upgrade resulted in increased discrimination capacity of close male relatives. Abstract: With the new 6-dye AmpFISTR ® Yfiler ® Plus amplification kit (Thermo Fisher Scientific, Waltham, MA, USA) a set of 25 Y-chromosomal short tandem repeat loci (Y-STRs), including seven rapidly mutating Y-STRs (RM Y-STRs), is now available for forensic DNA typing. In this study we present our validation data for the AmpFISTR ® Yfiler ® Plus amplification kit and show the results of Y-chromosomal typing of 425 unrelated male individuals from two Austrian populations (Salzburg and Upper Austria) with the AmpFISTR ® Yfiler ® Plus amplification kit. Forensic parameters were calculated and compared for four Y-STR marker sets. We also typed five brother pairs to evaluate the power of discrimination for related individuals. The AmpFISTR ® Yfiler ® Plus (Yfiler Plus) kit appeared to be unimpaired by typical inhibitors such as hematin and humic acid or by large amounts of female components. An upgrade of analyzed markers resulted in increased discrimination capacity that is crucial for forensic trace analysis.